2018
DOI: 10.3390/en11092346
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impacts of Solar-Photovoltaic and Solar-Thermal Systems with Life-Cycle Assessment

Abstract: The demand for clean energy is strong, and the shift from fossil-fuel-based energy to environmentally friendly sources is the next step to eradicating the world’s greenhouse gas (GHG) emissions. Solar energy technology has been touted as one of the most promising sources for low-carbon, non-fossil fuel energy production. However, the true potential of solar-based technologies is established by augmenting efficiency through satisfactory environmental performance in relation to other renewable energy systems. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 55 publications
(78 reference statements)
0
40
0
1
Order By: Relevance
“…Nevertheless, the CExC values obtained here could be underestimated due to the exclusion of indirect resource consumption during the technology manufacturing stage, specifically for solar photovoltaic panels and wind turbines. In this sense, several studies highlighted the high primary exergy consumption during PV modules production [59][60][61]. Furthermore, the results reported also demonstrated that the manufacturing stage varies as a function of the material used in PV, implying variation from 22% to 81% of total exergy consumption [59,60].…”
Section: Cumulative Exergy Consumption (Cexc) Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the CExC values obtained here could be underestimated due to the exclusion of indirect resource consumption during the technology manufacturing stage, specifically for solar photovoltaic panels and wind turbines. In this sense, several studies highlighted the high primary exergy consumption during PV modules production [59][60][61]. Furthermore, the results reported also demonstrated that the manufacturing stage varies as a function of the material used in PV, implying variation from 22% to 81% of total exergy consumption [59,60].…”
Section: Cumulative Exergy Consumption (Cexc) Analysismentioning
confidence: 99%
“…Furthermore, the results reported also demonstrated that the manufacturing stage varies as a function of the material used in PV, implying variation from 22% to 81% of total exergy consumption [59,60]. In addition, the Life Cycle Assessment (LCA) of the battery solar-PV manufacturing also depicted significant impacts on water resources depletion, land use and natural resources (minerals) [61]. The wind turbines are also characterized by high demand of natural resources (energy resources and material resources), as is demonstrated in most of the LCA impact methods [62][63][64].…”
Section: Cumulative Exergy Consumption (Cexc) Analysismentioning
confidence: 99%
“…Photovoltaics based power generation employs solar panels to produce power on both a standalone basis using batteries or on a grid-connected basis using an inverter and electrical utility lines. Currently, commercially available PV modules are considered as not highly efficient (with typical efficiencies of~16%), and thus there are intense research and development efforts for the development of new technological solutions to the challenge of producing commercial PV with increased efficiencies [10,19]. The rapid decline in installed costs (prices per installed MW have fallen by about 60% since 2008) has significantly improved the economic viability of PV around the world, with the global installed capacity escalated at 402 GW in 2017 compared to 8 GW back in 2007 [2,20].…”
Section: Photovoltaicsmentioning
confidence: 99%
“…By optimizing the system performance based only on GHG emissions, new environmental burdens may be introduced from other environmental emissions (e.g., NO x and SO 2 ). A holistic or system-level perspective is therefore essential in the assessment, and the range of emission types included in a study may critically affect the outcome [9][10][11].LCA is the methodology to be used when comparing the environmental performance (strengths and weaknesses) of different energy technologies, among them renewable systems. The idea behind a life cycle perspective in the context of power generation is that the environmental impacts of electricity are not only due to the power production process itself, but also originate from the production chains of installed components, materials used, energy carriers, and necessary services.…”
mentioning
confidence: 99%
See 1 more Smart Citation